(SHM)-H-2 in Some European Countries - Limongelli, Maria Pina (2019)
This paper compiles and describes the national initiatives and projects on Seismic Structural Health Monitoring ((SHM)-H-2) active in a number of European countries. Sensors networks and typical layouts, data processing techniques and policies adopted for the management of alerts are described for the different national programs. The different policies adopted for the access to data are also described. Applications to buildings, bridges or cultural heritage constructions are used to describe in detail the seismic SHM systems installed in Italy, France, Greece and Portugal.